WASHING UP OF SEPARATE COATINGS IN MANUFACTURING CASES FROM ALUMINUM ALLOYS BY PRESSURE CASTING - A. A. Pivovarchyk; A. M. Mikhaltsov (Литьë и металлургия)
The article presents the results of research of the influence of technological modes of injection molding of aluminum alloys, such as the pressing speed, molding time in a mold, the method of depositing a separation coating on the mold surface and the composition of the lubricant on the erosion resistance of the separation coatings. It is established that the pressing speed is most significant from the factors that influence the thickness of the lubricating layer forming on the working surface of the mold. When using water-based coatings, the thickness of the separation coating layer on the mold surface is reduced from 19,0 to 3,2 mm; for fatty separation coatings with a powder filler from 40,0 to 7,0 mm. It was also found that the minimum thickness of the lubricating layer of the separation coating is observed in the gate area and is in the range from 1,2 to 1,7 mm for the investigated water-emulsion separation coatings and 6,0 to 11,0 mm for fatty greases. It is shown that when the separation coatings are applied by a mechanized method, the thickness of the lubricating layer is 2,0–2,2 times lower than when applying lubricant manually.